Gender and potential impacts on decision-making in arbitration: experiences from Germany in an international field. Issue 1 (2nd January 2022) - Schultz, Ulrike
ABSTRACT: Women lawyers are still grossly underrepresented in arbitration which is a field of big business where high incomes are made. It is dominated by big law firms. Till two decades ago the number of women in these firms was small, but as in many countries women meanwhile outnumber men in legal education, the law firms have to hire women increasingly as they need the female talent. On associate level women meanwhile have a fair share. The question arose amongst practitioners which impact an intrusion of women in this formerly male field would have. Can women negotiate as successfully as their male colleagues and do they judge differently? That means that the questions dealt with over many years in projects on gender and judging appeared in a new context.